Imaging and Management of Childhood Ascariasis - Banderker, Ebrahim; Arnold, Marion; Cox, Sharon; Gaxa, Luvo (Journal of Pediatric Infectious Diseases, 2017)
The human-specific roundworm Ascaris lumbricoides continues to cause significant morbidity and mortality across the world, especially within Asia, South America, and Africa, despite the success of mass eradication programs. Most childhood worm infestations are relatively asymptomatic. Children can, however, be burdened by ascariasis and its negative nutritional impact. Heavy worm loads are complicated by intestinal obstruction, bowel necrosis, and bowel perforation. Less frequently, biliary obstruction and its complications may also occur. Radiological detection of complications allow for early institution of the largely successful nonoperative management followed by curative antihelminthics. Imaging is essential in the monitoring and detection of ominous signs that direct emergency surgical intervention and follow-up.
Keywords: pediatric; roundworm; Ascaris lumbricoides; intestinal ascariasis; hepaotobiliary ascariasis; bowel obstruction